Comparative Study on the Coating Properties of Hot - Formed Steel with Different Coatings - ZHOU Lin, WANG Hui, JIANG Jin - jing (Cailiao Baohu, 2021)
In recent years, coated hot - formed steel parts have been widely used in car bodies, and a good coating performance is a key factor for these parts to obtain good corrosion resistance. For this, in this work, the coating simulation test, scanning electron microscope, phosphating film retest, cyclic corrosion test and other methods were used to contrastively study the phosphating performance and corrosion resistance after coating of zinc - based coating hot - formed steel and aluminum - silicon coating hot - formed steel. Results show that: (1) The phosphating film of zinc - based coating hot - formed steel was more uniform than that of aluminum - silicon coating hot - formed steel, which could meet the general standard requirements of current car manufacturers. (2)Zinc - based coating hot - formed steel possessed better scratch corrosion performance after electrophoretic coating.